Content And Calorific Value Of Fermentation Of Bioethanol From Pineapple Waste With Variation Of Manufacturing Time - Majedi, Farid - (International Journal of Science, Engineering, and Information Technology, 2024)
To solve this increasing energy need, it is proposed to use bioenergy as an alternative energy source to replace fossil fuels. One form of bioenergy used is bioethanol. Bioethanol is a biochemical liquid from the sugar fermentation process and a source of glucose, cellulose and starch or carbohydrates using the help of microorganisms. Bioethanol can be made from plant products such as sap, tubers and fruit. Based on the description that has been presented, researchers are interested in conducting research on the content and calorific value of bioethanol fermented from pineapple fruit waste with variations in the length of production time. This research is an experiment that utilizes pineapple waste material to be used as bioethanol, through several processes, namely the hydrolysis process, fermentation process and distillation process. The aim of this research was to determine the calorific value and alcohol content. For the materials used, 2 kg of pineapple fruit waste, 10 liters of distilled water, 100 ml of amylase enzyme, 400 grams of yeast and for variations in the fermentation time, namely 7 days and 14 days. The research results obtained the highest alcohol content with a fermentation time of 14 days with an alcohol content of 67%. Fermentation time of 7 days produces an alcohol content of 54%. The highest calorific value with a fermentation time of 14 days is 3393.423 cal/gram, while the calorific value with a fermentation time of 7 days is 2214.873 cal/gram.Keywords: Bioethanol, Pineapple Waste, Calorific Value, Alcohol Content.